Perioperative Optimization of Senior Health in Spine Surgery: Impact on Postoperative Delirium. Issue 5 (31st December 2020) - Pernik, Mark N.; Deme, Palvasha R.; Nguyen, Madelina L.; Aoun, Salah G.; Adogwa, Owoicho; Hall, Kristen; Stewart, Nick A.; Dosselman, Luke J.; El Tecle, Najib E.; McDonald, Shelley R.; Bagley, Carlos A.; Wingfield, Sarah A.
Abstract : Background: Delirium is a common postoperative complication in geriatric patients, especially in those with underlying risk factors. Multicomponent nonpharmacologic interventions are effective in preventing delirium, however, implementation of these measures is variable in perioperative care. The aim of our study was to assess the impact of our Perioperative Optimization of Senior Health Program (UTSW POSH ) on postoperative delirium in patients undergoing elective spine surgery. Study Design: The UTSW POSH program is an interdisciplinary perioperative initiative involving geriatrics, surgery, and anesthesiology to improve care for high‐risk geriatric patients undergoing elective spine surgery. Preoperatively, enrolled patients (n = 147) were referred for a geriatric assessment and optimization for surgery. Postoperatively, patients were co‐managed by the primary surgical team and the geriatrics consult service. UTSW POSH patients were retrospectively compared to a matched historical control group (n = 177) treated with usual care. Main outcomes included postoperative delirium and provider recognition of delirium. Results: UTSW POSH patients were significantly older (75.5 vs 71.5 years; P < .001), had more comorbidities (8.02 vs 6.58; P < .001), and were more likely to undergo pelvic fixation (36.1% vs 17.5%; P < .001). The incidence of postoperative delirium was lower in the UTSW POSH group compared to historical controls, although not statistically significant (11.6% vs 19.2%; P = .065). Delirium was significantly lower in patients who underwent complex spine surgery (≥4 levels of vertebral fusion; N = 106) in the UTSW POSH group (11.7% vs 28.9%, P = .03). There was a threefold increase in the recognition of postoperative delirium by providers after program implementation, (76.5% vs 23.5%; P = .001). Conclusions: This study suggests that interdisciplinary care for high‐risk geriatric patients undergoing elective spine surgery may reduce the incidence of postoperative delirium and increase provider recognition of delirium. The benefit may be greater for those undergoing larger procedures.